Effectiveness of crop-waste compost on a Eutric Ferralsol - Amoding, Alice; Tenywa, John Stephen; Ledin, Stig; Otabbong, Erasmus (Journal of Plant Nutrition and Soil Science, 2011)
Lack of environmentally safe handling of garbage is a growing problem in urban sub-Saharan Africa (SSA). Composting the garbage for soil-fertility management presents an opportunity for reducing the risks of environmental pollution. This study aimed at evaluating the agronomic effectiveness and nutrient-utilization efficiency of urban market crop-waste compost on a Eutric Ferralsol. The study was conducted in central Uganda with treatments including compost applied at 0, 5, and 10 t ha–1 (d.w. basis); inorganic N fertilizer at rates of 0, 40, and 80 kg ha–1 and inorganic P fertilizer at 0, 9, and 18 kg ha–1. Maize (Zea mays L.), variety Longe 4 was used as the test crop. The nutrient quality of the compost was medium with total N of 0.9% and total P of 0.45%. Compost significantly increased plant height, LAI, stover weight, and grain yield; however, there were no significant differences between the 5 and 10 t ha–1 rates. Nitrogen also had a significant effect on LAI and stover yield, though there was no significant difference between the 40 and 80 kg ha–1 rates. Likewise, P increased plant height with no significant difference between the 9 and 18 kg ha–1 rates. Mineral N at 40 kg ha–1 led to the highest increase in N uptake by plants (76%) above the control. Nitrogen- and P-utilization efficiencies for the 5 t ha–1 compost rate were more than twice that of the 10 t ha–1 rate. The highest P-utilization efficiency (69%) was obtained where 9 kg ha–1 P was applied with 40 kg ha–1 N, while the highest N-utilization efficiency (48%) was obtained with the 5 t ha–1 compost applied together with N at 40 kg ha–1. From the above studies, it is clear that effectiveness of the 5 t ha–1 compost rate is the most promising.
Keywords: nitrogen / phosphorus / nutrient-utilization efficiency / uptake / sub-Saharan agriculture